Pengaruh Mekanisme Good Governance Terhadap Pengelolaan Dana Desa di Desa Jatikalen Kabupaten Nganjuk Periode 2023 - Azizah, Windi Nur; Linawati, Linawati; Sugeng, Sugeng (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The village governance can serve as an example in realizing Good Governance, where a strong and positive relationship between the village administration and the community can enhance community participation. This research focuses on whether accountability, transparency, participation, and responsibility affect the management of village funds durung the 2023 periode in Jatikalen Village. The purpose of this research is to determine the impact of Good Governance factors on the management of village funds. The research metod used is quantitative associative and is conducted in Jatikalen Village, Nganjuk Regency. The variables studied inclued Accountability, Transparancy, Participation, Responsibility, and Village Fund Management. The research population consists of various village elements such as the village Head, Village Officials, Staff, BPD, PKK, Village Cadres, RT/RW, and Youth Organizations, totaling 60 respondents. Data wew collected through questionnaires. Validity tests, reliability tests, classical assumption tests, determination coefficient tests, and hypothesis test were used in data analysis. The result show that Accountability. Transparence, participation, and responsilibity have a significant effect, both partially and simultaneously, on the management of village funds in Jatikalen Village, Nganjuk Regency.